Pengaruh Penerapan Metode Inkuiri Terbimbing pada Pembelajaran IPA Terhadap Hasil Belajar Siswa - Utami Novita Lestari; Rohana Sufia; Ficky Dewi Ixfina; Risma Firda Diana (STKIP Andi Matappa Pangkep, 2023)
Learning implementation practically changes. Students are no longer the object of learning. The success of education is also determined by the teachers’ quality. If teachers can understand the process of acquiring knowledge, then they can determine appropriate learning strategies or methods, one of which is guided inquiry. Guided inquiry is a method that involves students actively discovering concepts independently. Research objective was to determine the implementation effect of the guided inquiry method on science learning outcomes in grade 5th of MI Al-Ghozali Surabaya. This research used quantitative methods. The research population was 39 students. The sampling technique used non-probability sampling. Data collection used interview sheets and tests. The data analysis used Pearson product moment and t-table test. The results showed, value of t-table 37 was 1.68. This shows t-count>t-table = 1.91>1.68. So Ho was accepted and it stated that there was an increase in student learning outcomes. Besides, rxy is bigger than r-table = 0.33617>0.316. It can be concluded that the guided inquiry method has a low effect on increasing student learning outcomes. This is also supported by the results of the coefficient of determination 11.3%, the remaining 88.7% (100% -11.3%) is influenced by other variables which were not examined by researchers.